Optimal timing for precutting in cases with difficult biliary cannulation - Takano, Yuichi; Nagahama, Masatsugu; Niiya, Fumitaka; Kobayashi, Takahiro; Yamamura, Eiichi; Maruoka, Naotaka (Endoscopy International Open, 2018)
Background and study aims In endoscopic retrograde cholangiopancreatography (ERCP), precutting is widely used when achieving biliary cannulation is difficult. However, no consensus has been reached with regard to the best time to initiate precutting.Patients and methods We retrospectively examined 63 patients who underwent precutting for naïve papilla with difficulty in biliary cannulation between 2009 and 2016. The outcomes of the early precut group (≤ 20 min from cannulation until initiating precutting) and the late precut group (> 20 min) were compared.Results Of the 63 patients, 17 (27 %) were in the early precut group and 46 (73 %) were in the late precut group; median time until the initiating precutting was 28 minutes (7 – 50). No significant difference was observed between the two groups in terms of clinical features (age, sex, and indication for ERCP), precutting method, and rate of pancreatic duct stent placement. Significantly higher rates of successful biliary cannulation were observed in the early precut group (16/17; 94 %) than in the late precut group (32/46; 70 %) (P < 0.05). In 13 patients in whom precutting was commenced after 40 minutes, the rate of successful biliary cannulation was very low at 53 % (7/13). No significant difference was found between the two groups in terms of incidence of complications (pancreatitis in 5 patients and bleeding in 1 patient).Conclusion In actual clinical practice, precutting is commenced approximately 30 minutes after cannulation; however, to successfully achieve biliary cannulation, precutting is recommended to be performed within 20 minutes. Precutting is effective when little inflammation and swelling of the ampulla of Vater is observed. This study was limited in that it was single-center, retrospective and had a small subject sample.